A cox microwave dielectric material with high dielectric constant and high q value and a preparation method thereof

CN119462127BActive Publication Date: 2026-11-03CHENGDU HONGMING & UESTC NEW MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411347935.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2026-11-03
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

现有技术中缺乏介电常数在50~60且具有高Q值的微波介质材料,尤其是在微波军用雷达及微波通讯系统中应用的中介电常数微波介质陶瓷材料,且现有材料成本较高。

Method used

Using the main crystalline phase material (1-x)BaTi4O9-xBaSm2Ti4O12, combined with the first modifiers MnCO3, Bi2O3, CeO2 and the second modifiers BaTiO3, SrTiO3, the dielectric constant and capacity temperature coefficient are adjusted through doping and glass composition to form a microwave dielectric material with low dielectric loss and high Q*f value.

Benefits of technology

Microwave dielectric materials with dielectric constants in the range of 50 to 60, dielectric loss < 2.5 × 10⁻⁴, capacity temperature coefficient < ± 30 ppm/℃, and Q*f > 20000 were prepared. These materials are low in cost and suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462127B_ABST
    Figure CN119462127B_ABST
Patent Text Reader

Abstract

The application discloses a COG microwave dielectric material with high dielectric constant and high Q value and a preparation method thereof, and relates to the technical field of microwave dielectric materials; the composition of the material is composed of a main crystal phase material, a first modifier, a second modifier and glass; the main crystal phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 Wherein, 0.1<=x<0.2; the first modifier is one or more of MnCO3, Bi2O3 and CeO2; the second modifier is one or more of BaTiO3 and SrTiO3; the microwave dielectric material prepared by the application has a dielectric constant in the range of 50-60, has high dielectric constant, low dielectric loss and high Q*f value, and has the COG characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microwave dielectric materials technology, specifically to a COG microwave dielectric material with a high Q value of dielectric constant and its preparation method. Background Technology

[0002] With the continuous development of microwave mobile communication, the research and application of microwave dielectric materials has become a hot research topic in the domestic materials field. Microwave dielectric materials are mainly used to fabricate resonators, filters, dielectric substrates, dielectric antennas, etc., and are widely used in military and civilian fields such as mobile phones, television satellite receivers, satellite broadcasting, and radar.

[0003] Microwave dielectric materials are mainly classified into three categories: low dielectric constant (<20), medium dielectric constant (20<ε<70), and high dielectric constant (>70). Low dielectric constant microwave dielectric materials were the earliest applied, possessing a very high Q*f value, and are primarily used in microwave substrates and high-end microwave components. Medium dielectric constant microwave dielectric materials are mainly used in satellite communication and mobile base stations, exhibiting a relatively high Q*f value. High dielectric constant microwave dielectric materials can significantly reduce the size of microwave devices; however, a higher dielectric constant is not always better, as excessively high dielectric constants can affect transmission losses. A suitable dielectric constant and a high Q*f value can meet the requirements of miniaturization design while reducing filter doping losses, resulting in better filter performance. Therefore, microwave dielectric materials with medium dielectric constants are widely used in the field of microwave mobile communication.

[0004] Intermediate microwave dielectric materials with dielectric constants of 20–70 are mainly used as dielectric resonators in microwave military radar and microwave communication systems. The miniaturization of mobile communication base stations urgently requires the research and development of new microwave dielectric ceramic materials with low frequency temperature coefficients, high Q values ​​(Q*f > 20000 GHz), and moderate εr. Currently, most research on intermediate microwave dielectric ceramics focuses on dielectric constants of 20–50, with very little research on dielectric constants between 50 and 60. There is also a lack of microwave dielectric materials with dielectric constants of 50–60 and high Q*f values ​​on the market. The microwave dielectric material with a dielectric constant of 50–60 disclosed in CN106045513A uses a SrO-CaO-MgO-ZnO-TiO2-Ta2O5 system, and the Ta2O5 content is as high as 63%–73%, resulting in high cost and limiting its widespread application. Summary of the Invention

[0005] This invention addresses the technical problem of the lack of microwave dielectric materials with a dielectric constant of 50–60 and a high Q value in the existing technology. The objective is to provide a COG microwave dielectric material with a high dielectric constant and Q value, and its preparation method, resulting in a dielectric constant in the range of 50–60 and a dielectric loss of <2.5 × 10⁻⁶. -4 Microwave dielectric material with a capacity temperature coefficient of <±30ppm / ℃, Q*f>20000, and C0G characteristics.

[0006] This invention is achieved through the following technical solution:

[0007] The first objective of this invention is to provide a COG microwave dielectric material with a high Q value of dielectric constant, the composition of which is composed of a main crystalline phase material, a first modifier, a second modifier and glass;

[0008] The main crystalline phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 Where 0.1 ≤ x < 0.2;

[0009] The first modifier is one or more of MnCO3, Bi2O3, and CeO2;

[0010] The second modifier is one or more of BaTiO3 and SrTiO3;

[0011] The glass is CaO-B2O3-SiO2 glass.

[0012] Furthermore, the weight percentages of each component in the COG microwave dielectric material are as follows:

[0013] 0wt%–0.7wt% MnCO3, 0wt%–0.75wt% Bi2O3, 0wt%–0.6wt% CeO2, 0wt%–3wt% SrTiO3, 0wt%–1.5wt% BaTiO3, 0wt%–0.5wt% CaO-B2O3-SiO2 glass, with the balance being the main crystalline phase material (1-x)BaTi4O9-xBaSm2Ti4O 12 .

[0014] Furthermore, the weight percentage of each component in the COG microwave dielectric material is as follows:

[0015] 0.1 wt% MnCO3, 0.1 wt% CeO2, 0.5 wt% SrTiO3, 0.1 wt% CaO-B2O3-SiO2 glass, and the balance being a main crystalline phase material, wherein the main crystalline phase material is 0.82BaTi4O9-0.18BaSm2Ti4O 12 .

[0016] Furthermore, the composition of the CaO-B2O3-SiO2 glass is as follows:

[0017] 38wt% ~ 45wt% CaCO3, 17wt% ~ 25wt% B2O3, 30wt% ~ 45wt% SiO2.

[0018] The second objective of this invention is to provide a method for preparing a COG microwave dielectric material with a high Q value of dielectric constant, comprising the following steps:

[0019] CaCO3, B2O3 and SiO2 are prepared according to the weight ratio, ball-milled for 5-7 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass.

[0020] Using BaCO3, TiO2, and Sm2O3 as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12 The chemical formula ingredients are ball-milled for 8 to 12 hours, then dried, sieved, and gradually heated to 1200℃ for calcination to obtain the main calcined block material;

[0021] The main sintering block material, the first modifier, the second modifier, and CaO-B2O3-SiO2 glass are mixed in proportion, ball-milled for 20-26 hours, dried, and sieved to obtain the ceramic material.

[0022] The ceramic material is granulated, pressed into discs, debinded, and gradually heated to 1270±20℃ and sintered for 2-4 hours to obtain COG microwave dielectric material.

[0023] Furthermore, in the preparation of CaO-B2O3-SiO2 glass, alcohol is used as the medium, and the mixture is ball-milled and mixed in a ratio of material:ball:alcohol = 1:5:1.

[0024] Furthermore, during the preparation of the main sintered block material, water is used as the medium, and the mixture is ball-milled and mixed in a ratio of material:ball:water = 1:3:2.

[0025] Furthermore, during the preparation of the ceramic material, water is used as the medium, and the material is ball-milled and mixed in a ratio of material:ball:water = 1:5:1.2.

[0026] Further, the process of granulating the ceramic material, pressing it into discs, and removing the adhesive includes:

[0027] The ceramic material is granulated by adding 8-9 wt% paraffin wax, pressed into discs using a hydraulic press, and then heated to 450°C to discharge the adhesive.

[0028] Furthermore, the heating rate is 2-4℃ / min.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] 1. This invention utilizes BaTi4O9 and BaSm2Ti4O 12 Composite, forming (1-x)BaTi4O9-xBaSm2Ti4O 12 Using this as the main crystalline phase, the main sintered material possesses an adjustable dielectric constant, low dielectric loss, and high Q*f value, resulting in a dielectric constant in the range of 50–60 and a dielectric loss <2.5 × 10⁻⁶. -4 Microwave dielectric material with a capacity temperature coefficient of <±30ppm / ℃, Q*f>20000, and C0G characteristics.

[0031] 2. To ensure a combination of high dielectric constant, low dielectric loss, and high Q*f value, this invention employs one or more of the following first modifiers: MnCO3, Bi2O3, and CeO2. This refines the grain size, reduces internal defects in the ceramic body, and makes the material structure uniform, thereby reducing dielectric loss. Furthermore, by incorporating one or more of the following second modifiers: BaTiO3 and SrTiO3, the capacity temperature change rate is adjusted using substances with both positive and negative change rates. This results in a material that combines high dielectric constant, low dielectric loss, and high Q*f value.

[0032] 3. By adding a small amount of glass, the present invention enables the liquid phase to form first during the sintering process, which coats the surface of the grains, accelerates the migration of materials and the discharge of gases, reduces porosity, and improves the density of the ceramic body.

[0033] 4. All raw materials used in this invention are domestically produced, and are inexpensive and plentiful. The preparation process of the ceramic material is simple, suitable for mass production, and has high application value. Attached Figure Description

[0034] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be considered as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort. In the drawings:

[0035] Figure 1 SEM image of ceramic material in formula 6;

[0036] Figure 2 SEM image of the ceramic body after sintering of ceramic material of formula 6;

[0037] Figure 3 XRD patterns of ceramic bodies for formulas 1, 4, 6, and 9. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the illustrative embodiments and descriptions of the present invention are only used to explain the present invention and are not intended to limit the present invention.

[0039] The following detailed description, with appropriate reference to the accompanying drawings, outlines an embodiment of a COG microwave dielectric material with a high Q-value dielectric constant and its preparation method according to the present invention. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art.

[0040] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. The range defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range.

[0041] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0042] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0043] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other substances not listed may also be included, or that only the listed substances may be included.

[0044] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0045] To achieve the objective of this invention, the technical solution of this invention is to provide a COG microwave dielectric material with a high Q value of dielectric constant, the composition of which consists of a main crystalline phase material, a first modifier, a second modifier and glass;

[0046] The main crystalline phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 Where 0.1 ≤ x < 0.2;

[0047] The first modifier is one or more of MnCO3, Bi2O3, and CeO2;

[0048] The second modifier is one or more of BaTiO3 and SrTiO3;

[0049] The glass is CaO-B2O3-SiO2 glass.

[0050] Among BaO-TiO2-based microwave dielectric materials, BaTi4O9 exhibits excellent performance and is a typical representative of intermediate microwave dielectric ceramics. Its dielectric constant is approximately 38, and its dielectric loss is 5 × 10⁻⁶. -4 The Q*f can reach over 30000, and the capacity temperature coefficient is approximately +50ppm / ℃, but its dielectric constant is difficult to reach 50. The BaSm2Ti4O in the BaO-Ln2O3-TiO2 system... 12 With a dielectric constant greater than 80, a Q*f value exceeding 8000 GHz, and a low capacitance temperature coefficient, this invention utilizes BaTi4O9 and BaSm2Ti4O9. 12 Composite, forming (1-x)BaTi4O9-xBaSm2Ti4O 12 The main crystalline phase gives the main sintered material an adjustable dielectric constant, low dielectric loss, and high Q*f value.

[0051] To ensure a high dielectric constant, low dielectric loss, and high Q*f value, one or more of the following modifiers—MnCO3, Bi2O3, and CeO2—are used as first modifiers to refine the grains and reduce internal defects in the ceramic body, thereby lowering dielectric loss. One or more of BaTiO3 and SrTiO3 are added as second modifiers to regulate the capacitance-temperature change rate by combining substances with positive and negative change rates. A small amount of glass is added to induce the formation of a liquid phase on the grain surface during sintering, accelerating material migration and gas expulsion, reducing porosity, and increasing the density of the ceramic body. Ultimately, a dielectric constant of 50–60 and a dielectric loss of <2.5 × 10⁻⁶ are achieved. -4 This invention relates to a microwave dielectric material with a capacity temperature coefficient of <±30ppm / ℃, Q*f>20000, and C0G characteristics. All raw materials used in this invention are domestically produced, inexpensive, and readily available, making it highly valuable for widespread application.

[0052] In a preferred embodiment, the weight percentages of each component of the COG microwave dielectric material are as follows:

[0053] 0wt%–0.7wt% MnCO3, 0wt%–0.75wt% Bi2O3, 0wt%–0.6wt% CeO2, 0wt%–3wt% SrTiO3, 0wt%–1.5wt% BaTiO3, 0wt%–0.5wt% CaO-B2O3-SiO2 glass, with the balance being the main crystalline phase material (1-x)BaTi4O9-xBaSm2Ti4O 12 .

[0054] In a preferred embodiment, the weight percentages of each component of the COG microwave dielectric material are as follows:

[0055] 0.1 wt% MnCO3, 0.1 wt% CeO2, 0.5 wt% SrTiO3, 0.1 wt% CaO-B2O3-SiO2 glass, and the balance being a main crystalline phase material, wherein the main crystalline phase material is 0.82BaTi4O9-0.18BaSm2Ti4O 12 Experiments have shown that, under this formulation, the dielectric ceramic material exhibits the best overall performance, combining a high dielectric constant, low dielectric loss, and a high Q*f value.

[0056] In a preferred embodiment, the CaO-B2O3-SiO2 glass has the following composition:

[0057] 38wt% ~ 45wt% CaCO3, 17wt% ~ 25wt% B2O3, 30wt% ~ 45wt% SiO2.

[0058] Meanwhile, this invention also provides a method for preparing a COG microwave dielectric material with a high Q value of dielectric constant, comprising the following steps:

[0059] CaCO3, B2O3 and SiO2 are prepared according to the weight ratio, ball-milled for 5-7 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass.

[0060] Using BaCO3, TiO2, and Sm2O3 as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12 The chemical formula ingredients are ball-milled for 8 to 12 hours, then dried, sieved, and gradually heated to 1200℃ for calcination to obtain the main calcined block material;

[0061] The main sintering block material, the first modifier, the second modifier, and CaO-B2O3-SiO2 glass are mixed in proportion, ball-milled for 20-26 hours, dried, and sieved to obtain the ceramic material.

[0062] The ceramic material is granulated, pressed into discs, debinded, and gradually heated to 1270±20℃ and sintered for 2-4 hours to obtain COG microwave dielectric material.

[0063] The grinding balls used are Φ7.5 zirconium balls.

[0064] In a preferred embodiment, when preparing CaO-B2O3-SiO2 glass, alcohol is used as the medium, and the mixture is ball-milled in a ratio of material:ball:alcohol = 1:5:1.

[0065] As a preferred embodiment, water is used as the medium in the preparation of the main sintering block material, and the mixture is ball-milled and mixed in a ratio of material:ball:water = 1:3:2.

[0066] In a preferred embodiment, water is used as the medium during the preparation of the ceramic material, and the mixture is ball-milled and mixed in a ratio of material:ball:water = 1:5:1.2.

[0067] As a preferred embodiment, granulating the ceramic material, pressing it into discs, and removing the adhesive includes:

[0068] The ceramic material is granulated by adding 8-9 wt% paraffin wax, pressed into discs using a hydraulic press, and then heated to 450°C to discharge the adhesive.

[0069] As a preferred embodiment, the heating rate is 2-4℃ / min.

[0070] The technical solution of the present invention will be further described in detail below with reference to the embodiments.

[0071] It should be noted that, unless otherwise specified, the experimental methods used in the embodiments are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0072] Example 1

[0073] A method for preparing a COG microwave dielectric material with a high Q value of dielectric constant includes the following steps:

[0074] (1) The composition of CaO-B2O3-SiO2 glass is 40wt% CaCO3, 20wt% B2O3 and 40wt% SiO2. It is ball-milled with alcohol as medium at a ratio of material:ball:alcohol = 1:5:1 for 6 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass.

[0075] (2) Using BaCO3, TiO2, and Sm2O3 as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12The chemical formula for synthesizing the main crystalline phase sintered block with x = 0.13 was obtained by weighing the raw materials and pouring them into a ball mill jar. The raw materials were ball milled in a ratio of material:ball:water = 1:3:2 for 8 to 12 hours. The sintered blocks were then dried, sieved, and calcined at 1200°C at a rate of 3°C / min to obtain the main sintered block material.

[0076] (3) The main sintering block material, the first modifier, the second modifier, and the CaO-B2O3-SiO2 glass are prepared according to the formula in Table 1 (in g). After ball milling for 20-26 hours at a ratio of material:ball:water = 1:5:1.2, the materials are dried and sieved to obtain the ceramic material.

[0077] (4) Add (8-9) wt% paraffin to the prepared ceramic material and granulate it. Press it into a disc using a hydraulic press, then raise the temperature to 450°C at a rate of 2.5°C / min to discharge the adhesive. Then raise the temperature to (1270±20)°C at a rate of 3°C / min and sinter for 2-4 hours to obtain COG microwave dielectric material.

[0078] (5) The small-formula ceramic materials in Formulas 1 to 9 and Comparative Examples 1 to 4 were prepared by rolling process. The ceramic substrate green body with a thickness of (0.22±0.03) mm and a length and width of 60 mm × 60 mm was obtained by batching, rolling and slicing. The green body was placed on the firing plate and placed in the box furnace. The temperature was raised to 900℃ at a rate of 1℃ / min and held for 2 hours to remove the sticky material. Then the temperature was raised to 1250℃ at a rate of 3℃ / min and held for 3 hours to sinter the ceramic substrate.

[0079] test:

[0080] 1. Discs: The dielectric constant and dielectric loss of the discs are tested using an impedance analyzer, the temperature coefficient of capacitance is tested using a high and low temperature chamber, and the insulation resistance and insulation strength of the products are tested using an insulation resistance meter and a withstand voltage meter.

[0081] 2. Ceramic substrate: The Q*f value was tested at 5.1 GHz using a network analyzer via the open cavity method. The testing methods for capacitance temperature coefficient, insulation resistance, and insulation strength were the same as those for wafers.

[0082] Comparative Example 1

[0083] The difference between this comparative example and formulation 6 in Example 1 is that no first modifier is added.

[0084] Comparative Example 2

[0085] The difference between this comparative example and formulation 6 in Example 1 is that no second modifier is added.

[0086] Comparative Example 3

[0087] The difference between this comparative example and formulation 6 in Example 1 is: (1-x)BaTi4O9-xBaSm2Ti4O 12 In the given information, x = 0.4.

[0088] Comparative Example 4

[0089] The difference between this comparative example and formulation 6 in Example 1 is: (1-x)BaTi4O9-xBaSm2Ti4O 12 In the given information, x = 0.2.

[0090] Table 1. Dielectric Ceramic Material Formulation

[0091]

[0092] The formulations in Table 1 were tested. The dielectric constant, dielectric loss, insulation resistance and insulation strength, and capacitance temperature change rate were tested using wafers, while the Q*f value was tested using substrates. The results are shown in Table 2.

[0093] Table 2. Properties of ceramic materials for each formulation

[0094]

[0095] Figure 1 This is a SEM image of the ceramic material in Formula 6. The image shows that the ceramic powder particles are of varying sizes and have good uniformity, which is beneficial for densification during sintering after molding. Figure 2 The image shows a SEM image of the ceramic body after sintering the ceramic material of Formula 6. As can be seen from the image, the ceramic grains are elongated and interwoven, and the ceramic body has few pores and high density.

[0096] Figure 3 The figures show the XRD patterns of ceramic bodies from formulas 1, 4, 6, and 9. As can be seen from the figures, the main crystalline phase system of these formulas is BaTi4O9-BaSm2Ti4O. 12 Composite host phase.

[0097] As can be seen from Table 2, the formulations in the examples all have high dielectric constants, low dielectric loss, and high Q*f values ​​in the intermediate microwave dielectric material. Among them, formulation 6 has the best overall performance.

[0098] To further verify the combined effect of the first and second modifiers, comparative examples 1 and 2 were set up for verification. As can be seen from the data in Table 2, the Q*f value of comparative example 1 is lower than that of formulation 6 without the first modifier, and the dielectric constant of comparative example 2 is lower than that of formulation 6 without the second modifier.

[0099] To further verify the influence of the value of x, comparative examples 3 and 4 were set up. As can be seen from the data in Table 2, when x ≥ 0.2 in the main crystalline phase material, the dielectric loss increases, the Q*f value decreases significantly and is < 20000 GHz, which does not meet the requirements.

[0100] Due to the superior overall performance of Formula 6, its scale-up verification was conducted. A ceramic substrate green body with a thickness of (0.22±0.03) mm and dimensions of 60 mm × 60 mm was prepared using a casting process involving batching, casting, lamination, isostatic pressing, and cutting. The green body was placed on a firing plate and then placed in a box furnace. The temperature was increased to 900℃ at a rate of 1℃ / min and held for 2 hours to remove adhesion. The temperature was then increased to 1250℃ at a rate of 3℃ / min and held for 3 hours for sintering to obtain the ceramic substrate. At 5.1 GHz, its dielectric constant, dielectric loss, and Q*f value were tested using an open-cavity resonant method with a network analyzer. Other properties were tested using the same method as the wafer test. The results are shown in Table 3.

[0101] Table 3, Properties of the ceramic substrate for formulation 6

[0102]

[0103] As can be seen from the data in Table 3, when the sample was prepared by expanding the dosage of Formula 6, the dielectric constants of the five samples were all at a high level, and the Q*f values ​​were also high.

[0104] Finally, it should be noted that the above specific embodiments are only used to describe the purpose, technical solution, and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation of the present invention and is not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the foregoing specific embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions or improvements can be made to some or all of the technical features. These modifications, equivalent substitutions, and improvements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A COG microwave dielectric material with a high Q value of dielectric constant, characterized in that, Its composition consists of a main crystalline phase material, a first modifier, a second modifier, and glass; The main crystalline phase material is (1-x)BaTi4O9-xBaSm2Ti4O 12 Where 0.1 ≤ x < 0.2; The first modifier is one or more of MnCO3, Bi2O3, and CeO2; The second modifier is one or more of BaTiO3 and SrTiO3; The glass is CaO-B2O3-SiO2 glass; The weight percentages of each component in the COG microwave dielectric material are as follows: 0wt%~0.7wt% MnCO3, 0wt%~0.75wt% Bi2O3, 0wt%~0.6wt% CeO2, 0wt%~3wt% SrTiO3, 0wt%~1.5wt% BaTiO3, 0.1wt%~0.5wt% CaO-B2O3-SiO2 glass, balance being the main crystalline phase material (1-x) BaTi4O9-xBaSm2Ti4O 12 .

2. The COG microwave dielectric material with high Q-value dielectric constant according to claim 1, characterized in that, The weight percentages of each component in the COG microwave dielectric material are as follows: 0.1 wt% MnCO3, 0.1 wt% CeO2, 0.5 wt% SrTiO3, 0.1 wt% CaO-B2O3-SiO2 glass, and the balance being a main crystalline phase material, wherein the main crystalline phase material is 0.82BaTi4O9-0.18BaSm2Ti4O 12 .

3. A COG microwave dielectric material with a high Q value of dielectric constant according to any one of claims 1-2, characterized in that, The composition of the CaO-B2O3-SiO2 glass is as follows: 38wt%~45wt%CaCO3, 17wt%~25wt%B2O3, 30wt%~45wt%SiO2.

4. The method for preparing a COG microwave dielectric material with a high Q value as described in any one of claims 1-3, characterized in that, Includes the following steps: CaCO3, B2O3 and SiO2 are prepared according to the weight ratio, ball-milled for 5-7 hours, dried and sintered at 650±20℃ to form CaO-B2O3-SiO2 glass. Using BaCO3, TiO2, and Sm2O3 as raw materials, according to (1-x)BaTi4O9-xBaSm2Ti4O 12 The chemical formula ingredients are ball-milled for 8-12 hours, then dried, sieved, and gradually heated to 1200℃ for calcination to obtain the main calcined block material; The main sintering block material, the first modifier, the second modifier, and CaO-B2O3-SiO2 glass are mixed in proportion, ball-milled for 20-26 hours, dried, and sieved to obtain the ceramic material. The ceramic material is granulated, pressed into discs, debinded, and gradually heated to 1270±20℃ and sintered for 2~4 hours to obtain COG microwave dielectric material.

5. The method for preparing a COG microwave dielectric material with a high Q value of dielectric constant according to claim 4, characterized in that, In the preparation of CaO-B2O3-SiO2 glass, alcohol is used as the medium, and the mixture is ball-milled in a ratio of material:ball:alcohol = 1:5:

1.

6. The method for preparing a COG microwave dielectric material with a high Q value of dielectric constant according to claim 4, characterized in that, When preparing the main sintering block material, water is used as the medium, and the mixture is ball-milled and mixed in a ratio of material:ball:water = 1:3:

2.

7. The method for preparing a COG microwave dielectric material with a high Q value of dielectric constant according to claim 4, characterized in that, When preparing the ceramic material, water is used as the medium, and the mixture is ball-milled and mixed in a ratio of material:ball:water = 1:5:1.

2.

8. The method for preparing a COG microwave dielectric material with a high Q value of dielectric constant according to claim 4, characterized in that, The process of granulating ceramic material, pressing it into round discs, and removing adhesive includes: The ceramic material is granulated by adding 8-9 wt% paraffin wax, pressed into discs using a hydraulic press, and then heated to 450℃ to discharge the adhesive.

9. The method for preparing a COG microwave dielectric material with a high Q value of dielectric constant according to claim 4, characterized in that, The heating rate is 2-4℃ / min.

Citation Information

Patent Citations

  • Middle-dielectric constant high-quality factor microwave dielectric ceramic and preparation method thereof

    CN106045513A

  • Two-phase compound microwave medium ceramic material and preparation method thereof

    CN102757219A

  • Microwave dielectric ceramic material and preparation method

    CN111153694A